Detection Of Ras GTPase Protein Radicals Through Immuno-Spin Trapping - Davis, Michael F. (2012)
Over the past decade immuno-spin trapping (IST) has been used to detect and identify protein radical sites in numerous heme and metalloproteins. To date, however, the technique has had little application toward non-metalloproteins. In this study, we demonstrate the successful application of IST in a system free of transition metals and present the first conclusive evidence of ·NO-mediated protein radical formation in the HRas GTPase. HRas is a non-metalloprotein that plays a critical role in regulating cell growth control. Protein radical formation in Ras GTPases has long been suspected of initiating premature release of bound guanine nucleotide. This action results in altered Ras activity both in vitro and in vivo. As described herein, successful application of IST may provide a means for detecting and identifying radical-mediated Ras activation in many different cancers and disease states where Ras GTPases play an important role.